EATMOT Project: Eating motivations in different parts of the world, and particularly in countries from the Mediterranean Area - Guiné, Raquel (2018)
The EATMOT Project is a multinational study about different eating motivations, and that is being carried out in 18 countries. The project addresses several types of factors that are related to food choice and consumption patterns, and that may in some extent condition the eating motivations, namely health related factors; economic and availability aspects; emotional determinants; social, cultural and religious influences; marketing and advertising campaigns and finally environmental concerns. The study is based on a questionnaire that was prepared purposely for the project, and therefore adequate to evaluate the aspects that determine the objectives highlighted. The study is coordinated by Portugal and involves a team of about 70 researchers from 16 countries, distributed as follows: Argentina, Brazil and United States in the American continent; Egypt in African continent; and the remaining countries in Europe: Croatia, Greece, Hungary, Italy, Latvia, Lithuania, Netherlands, Poland, Portugal, Serbia, Slovenia and Romania. The collected results surpass 12 thousand cases and allow, among many other studies, characterizing the eating motivations in different parts of the world, including the Mediterranean surrounding countries or countries which are typically linked to the Mediterranean diet, specifically: Croatia, Egypt, Italy, Greece or Portugal.